Cuidados de enfermería en pacientes neurocríticos - Llongo Hidalgo, Deysi Magaly (2025)
Neurocritical patients suffer serious affectations in the central nervous system as well as other vital systems, due to severe trauma or degenerative diseases. So, specialized care in Intensive Care Units focuses on significantly reducing side effects, which is why the objective of this study is to identify nursing care in neurocritical patients. For which the use of the qualitative study modality was considered, which was supported by research such as descriptive, bibliographic applied while the method used was the PRISMA to structure the literature review on nursing care in neurocritical patients. For this an exhaustive search was carried out in scientific databases followed by a rigorous selection of relevant studies through a critical evaluation of the quality of the included articles and an analytical synthesis of the findings, allowing to obtain a comprehensive and well-founded vision of nursing interventions in this population, ensuring the validity and reliability of the results. Interventions based on continuous monitoring of intracranial pressure, optimization of mechanical ventilation, controlled administration of sedation and analgesia allow to stabilize the patient's clinical condition and prevent complications, so the prevention of nosocomial infections through the application of aseptic and antisepsis measures reduce the morbidity and mortality of this population. Concluding that strategies such as the regulation of body temperature, early mobilization, use of standardized neurological scales improve the neurological functionality and recovery of the patient.